Terms and Need Strategic Cooperation Mechanisms of Social and Economic Systems of the Region - Novosyolova, Natalya N.; Novoselov, Sergey N.; Tereshchenko, Eleonora Y.; Khasheva, Zarema M.; Lukyanova, Anna Y. (International Journal of Economics and Financial Issues, 2016)
The increasing complexity of the socio-economic systems and the increase in the state’s functions in modern regional space becoming more common complex, multi-level strategic cooperation mechanisms. In such structures, the main elements of the control system are divided into several levels. Management levels are organizationally separate elements detected in the territorial structures of governance, for example, the subject of the Federation, municipal formation. Between the different levels of the system of separation of powers, responsibilities and functions of the power vertical. Within the framework of the powers assigned to them elements of the system have the right to independent decision-making. Developing of the Russian Federation system of market relations qualitatively increased value, role, authority and responsibility of regions to ensure the functioning and development of the territories, the growth of living standards of the population living in them. Enhanced functions of the organs of power in the federal subjects is accompanied by the simultaneous complexity of the mechanism of management decision-making, and the increasing influence of the variability of environmental factors. Under these circumstances, the effective activities of the regional administrations are not possible without the coordination and integration of their efforts, which can promote inter-regional cooperation. Keywords: regional economy, social and economic system, management mechanism JEL Classifications: Q27, R12, R58